A nationwide analysis of physical inactivity and sedentary behavior among stroke survivors in Korea - Lee, Eung-Joon; Jeong, Hae-Bong; Bae, Jeonghoon; Kim, Seung-Jae (Scientific reports, 2025)
This study aimed to identify key predictors of physical inactivity and prolonged sedentary behavior among stroke survivors (SSs) using data from the 2016–2020 Korea National Health and Nutrition Surveys. Of the 28,146 participants, 633 had a history of stroke. The results showed that SSs were significantly more likely to be physically inactive and spend longer sedentary times than controls. Multivariate analysis identified that age ≥ 80 years (adjusted odds ratio [aOR] = 5.45, 95% confidence interval [CI] 1.96–15.15), lower education level (≤ 9 years) (aOR = 2.18, 95%CI 1.13–4.18), and living in rural areas (aOR = 1.91, 95%CI 1.11–3.29) were associated with aerobic physical inactivity. Female sex (aOR = 2.36, 95%CI 1.28–4.35) and lower education (aOR = 2.31, 95%CI 1.01–5.34) were linked to insufficient resistance exercises (≤ 1 day per week). Long sedentary time (≥ 8 h daily) was associated with being economically inactive (aOR = 1.90, 95%CI 1.21–2.96), single (aOR = 1.68, 95%CI 1.07–2.64), and perceiving oneself as unhealthy (aOR = 1.59, 95%CI 1.01–2.49). These findings highlight the need for targeted interventions, including community-based exercise programs and policy initiatives, to reduce sedentary behavior and promote physical activity among SSs. Implementing accessible and tailored rehabilitation strategies may help mitigate long-term health risks in this population.